The effect of Sharia bank knowledge, promotion, and facilities on savings decisions at Sharia banks with savings interest as mediation variables - Oriesta Dhea Budi Utamy; Ratieh Widhiastuti (Journal of Islamic Economics, Management, and Business (JIEMB), 2019)
Purpose - The purpose of this study is to explain the effect of Sharia bank knowledge, promotion, and facility on saving decisions in Shariah bank both directly and through saving interest.Method - The population in this study is the students of Sharia banking department at Islamic Business and Economics Faculty of IAIN Purwokerto Batch 2016/2017 of 106 students. All populations in this study were used as the sample. The technique of data collection in this study used questionnaires. Techniques of data analysis used descriptive statistic analysis and path analysis. Result - The results showed that Sharia bank knowledge, promotion, and facility give a positive and significant effect on saving decisions in Sharia Bank. Saving interest can mediate Sharia bank knowledge, promotion, and facility on saving decisions in Sharia Bank.Implication - Suggestion from this study are expected that Sharia Bank can fix the facility and improve promotions so that the customer candidate can know what kind of product offered so that saving interest and saving decision in Sharia Bank can be improved.Originality - This study adds Islamic bank knowledge and saving interest variable as the intervening variable.